Modern geothermal HVAC engineering and control applications - Egg, Jay; Cunniff, Greg; Orio, Carl D. (New York McGraw-Hill Education, 2013)
"With a focus on market needs and customer goals, this practical guide explains how to realize the full potential of geothermal HVAC by integrating hydronic systems and controls at maximum capacity. This book explains how to engineer and specify geothermal HVAC for building projects in varying geographic regions. Typical details on control parameters are provided. By using the proven methods in this innovative resource, you will be able to develop highly efficient, long-lasting, and aesthetically pleasing geothermal HVAC systems. "--Back cover.
Low-Temperature Geothermal or Earth Coupling -- Geothermal Heat-Pump Equipment -- Variations in Earth Coupling -- Application of Earth Coupling with Regard to Site Considerations -- Closed-Loop Earth Coupling and Fusion -- Plate-Frame Heat Exchanger: When Is It Needed? -- Standing Column and Open Geothermal Systems -- Fundamentals of Comfort, Psychrometrics, and Thermodynamics -- Heating, Ventilation, and Air-Conditioning System Basics -- Hydronic Heating, Ventilation, and Air-Conditioning System Equipment -- Variations and Improvements to Hydronic Systems -- Control Systems -- Load Sharing and Energy Recovery -- Calculating System Efficiencies -- Geothermal Rebates, Incentives, and Renewables Legislation.
Includes index.
Keywords: Ground source heat pump systems